Isolation and Molecular Identification of the Native Microflora on Flammulina velutipes Fruiting Bodies and Modeling the Growth of Dominant Microbiota (Lactococcus lactis) - Wei, Qi; Pan, Xinyuan; Li, Jie; Jia, Zhen; Fang, Ting; Jiang, Yuji (Frontiers in Microbiology, 2021)
The objective of this study was to isolate and identify the dominant microorganism in Flammulina velutipes fruiting bodies (FVFB) and to develop kinetic models for describing its growth. The native microflora community on FVFB was isolated and identified using morphological examination and high throughput sequencing analysis. FVFB presented complex microbial communities with the dominant microorganisms being Lactococcus lactis (L. lactis). Irradiated FVFB was inoculated with the isolated strain of L. lactis, and cultivated at various temperatures (4, 10, 16, 20, 25, 32, and 37°C). Three primary models, including the Huang, Baranyi, and Reparameterized Gompertz models, and three secondary models, including the Huang square-root, Ratkowsky square-root, and Arrhenius-type models, were developed and evaluated. With the lowest values of mean square error (MSE, 0.023-0.161) and root mean square error (RMSE, 0.152-0.401) values, Reparameterized Gompertz model was more suitable to describe the growth of L. lactis on FVFB than both Huang and Baranyi models. The Ratkowsky square root model provided more accurate estimation for the effect of temperature on the specific growth rate of L. lactis. The minimum growth temperature predicted by Ratkowsky square root model was -7.1C. The kinetic models developed in this study could be used to evaluate the growth behavior of L. lactis on FVFB and estimate the shelf-life of FVFB.